From Data to Strategy: Analysis of Profitability, Tangibility, and Liquidity in Building Capital Structure of Islamic Banks in Indonesia - Andriani, Wiwik; Djefris, Dedy; Zahara, Zahara (Universitas Batanghari Jambi, 2025)
This study investigates the impact of profitability, tangibility, and liquidity on the capital structure of Islamic banks in Indonesia from 2021 to 2023. Employing a quantitative approach, the research utilizes multiple linear regression analysis. The population consists of 13 Islamic commercial banks registered with the Financial Services Authority (OJK) during this period, with a purposive sampling method resulting in a sample of 12 banks. Data are gathered from secondary sources, specifically annual financial reports available on each bank's website. The findings reveal that while profitability and tangibility do not significantly influence capital structure, liquidity has a negative and significant impact on it. Improving liquidity management, adjusting financing policies, and focusing on operational efficiency to enhance profitability are essential. Additionally, communicating liquidity strategies to investors and training staff on liquidity risk management will support better decision-making within the bank. This research lies in its focus on Islamic banks in Indonesia, highlighting liquidity's negative impact on capital structure. It provides contemporary empirical data, practical recommendations for management, and contributes to the literature on financial practices in Islamic banking.